Appendix 4.16: Marcos Diary Entry, 27 January 1973 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
In the previous entries, Marcos claimed, in so many words, that he was ready to disregard or dismantle the Supreme Court if it becomes uncooperative. Here, he says that the Court has to be handled “with finesse” because it may become “the rallying point of the opponents of reform.” It seems that by this date, Marcos had come to consider the Supreme Court as his double-edged sword—potentially his ultimate legitimizer as well as the instrument of his regime’s dismantlement.